Pengembangan Media Pembelajaran Audio Visual dengan Menggunakan Aplikasi Canva pada Materi Sistem Gerak - Edieli Zebua (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to produce audio-visual learning media products, test the feasibility and find out the response of educators and students to the media by using the Canva application on motion system material at SMA Negeri 1 Tomohon. This research is a Research and Development (R&D) study that is used to develop and produce audio-visual media products using the Canva application on motion systems material at SMA Negeri 1 Tomohon. This type of planning and producing media research goes through 4 stages 1) the preparation stage; 2) design stage; 3) development stage; 4) trial and evaluation stage. The research subjects consisted of 28 students, 1 educator, 1 media expert and 1 material expert. Data collection instruments used validation sheets and questionnaires and analyzed data using due diligence, educator and student responses. The results showed that the assessment based on the validation of media experts got a percentage of eligibility, namely 93% in the very feasible category, no need for revision. As for the results of the field trials, 94% of educators and 96.5% of students were interested. In conclusion, learning media is appropriate and attracts the attention of students so that it is feasible to be used as a learning medium in SMA Negeri 1 Tomohon. Keywords: Audio Visual, Canva, Learning, Movement System